Kebijaksanaan dan Kepemimpinan Raja Salomo dalam Kitab 1 Raja-raja: Relevansinya bagi Kepemimpinan Modern - Benediktus James Widya Darmaka; Etty Justiana Saragih; Yustinus Jepri; Galuh Pria Utama (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2026)
The crisis of integrity, ethical disorientation, and the declining quality of strategic decision-making in contemporary leadership demand a robust and transhistorical normative foundation. The figure of King Solomon in ancient Israelite tradition represents a prototype of leadership legitimized by divine wisdom, making it critically relevant for scholarly examination. This study addresses the problem of how the construction of Solomon’s character and the praxis of his wisdom in Old Testament texts can be transformed into a conceptual paradigm for modern leadership without falling into historical romanticism. The objective of this research is to formulate a theoretical leadership model grounded in biblical wisdom through an analysis of Solomon’s character, theological orientation, and decision-making patterns. The method employed is a theological hermeneutical approach integrated with interdisciplinary literature studies, including leadership theory, public ethics, and Old Testament theology. The analysis focuses on key narratives that portray the judicial, administrative, and spiritual dimensions of Solomon’s leadership. The findings indicate that Solomon’s wisdom is theocentric, deliberative, and oriented toward distributive justice, thereby shaping an integrative and visionary model of leadership. The relevance of these findings lies in their capacity to offer a normative framework for leadership formation rooted in transcendent morality while remaining adaptive to modern social complexity. The novelty of this study resides in the formulation of a hermeneutical reconstruction model of Solomonic wisdom as a normative-strategic paradigm for the development of contemporary leadership theory based on sacred texts.